An Examination On Human Resource Management In Aligning To The Organizational Strategy - Ting Si Xue, Colin (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Human Resource Management has been proved to be an important element in organizing business. Every organization should have their own strategy. A study has been carried out to evaluate that Human Resource Management strategy is aligned to the organization strategy. In this paper, I have examined on how Starbucks uses Human Resource Management strategy to manage their business.